1996
DOI: 10.1046/j.1365-3083.1996.d01-69.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Specific Receptor for Interleukin‐8 from the Surface of Human Monocytes

Abstract: A specific receptor for interleukin-8 has been identified on the surface of human monocytes using 125I IL-8 as a probe. A binding kinetic pattern shows that saturation was attained after 90 min and that the receptor was distinct from the receptors of other cytokines (IL-L alpha, IL-2, TNF alpha, GMCSF) and FMLP. Scatchard analysis of the binding data shows that 7000-10,000 receptors /monocyte are present with an equilibrium Kd 7 x 10(-9) M. By immunoblot, the receptor for IL-8 showed a sharp band with approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, the chemotaxis was not observed in our preliminary study (data not shown), possibly because the IL-8 concentration in the culture supernatants was too low to attract T cells which express IL-8 receptors at a lower level than neutrophils (19,30,36). IL-8 receptors have also been detected on monocytes and natural killer cells (7,43). Thus far, we have not ruled out chemotactic effects of IL-8 on infiltrating lymphocytes and other immune cells in NPC tumors in vivo.…”
Section: Discussionmentioning
confidence: 61%
“…However, the chemotaxis was not observed in our preliminary study (data not shown), possibly because the IL-8 concentration in the culture supernatants was too low to attract T cells which express IL-8 receptors at a lower level than neutrophils (19,30,36). IL-8 receptors have also been detected on monocytes and natural killer cells (7,43). Thus far, we have not ruled out chemotactic effects of IL-8 on infiltrating lymphocytes and other immune cells in NPC tumors in vivo.…”
Section: Discussionmentioning
confidence: 61%
“…The observation that trophoblast cells secrete high levels of IL-8 and MCP-1, which are both known to be chemotactic for monocytes (33,34), suggests that trophoblast cells may regulate monocyte migration to the maternal-fetal interface. Using an in vitro migration assay, we first sought to determine whether the levels of IL-8 and MCP-1 that were detected in the trophoblast supernatants were sufficient to induce monocyte chemotaxis and transmigration.…”
Section: Monocytes Migrate Toward Lps-stimulated First Trimester Tropmentioning
confidence: 99%
“…33 Cells were incubated with increasing doses of 125 I Achatinin-H for 90 min at 4°C in the presence or absence of a 100-fold excess of unlabeled Achatinin-H. 125 I Achatinin-Hbound cells were separated from free 125 I Achatinin-H by layering the mixture onto a 5% sucrose solution followed by centrifugation at 12,857g for 10 min at 4°C. 34 Cell-bound radioactivity in the pellet was measured by a gamma counter. The number of receptors per cell was extrapolated by the intersection of the curve with the x axis, and the K d was obtained by dividing the number of receptors per cell by the bound/free ratio at the y axis intercept.…”
Section: Scatchard Analysismentioning
confidence: 99%